Public sector efficiency: an international comparison - António Afonso; Ludger Schuknecht; Vito Tanzi (European Central Bank (ECB), 2003)
We compute public sector performance (PSP) and efficiency (PSE) indicators, comprising a composite and seven sub-indicators, for 23 industrialised countries. The first four sub-indicators are "opportunity" indicators that take into account administrative, education and health outcomes and the quality of public infrastructure and that support the rule of law and a level playing-field in a market economy. Three other indicators reflect the standard "Musgravian" tasks for government: allocation, distribution, and stabilisation. The input and output efficiency of public sectors across countries is then measured via a non-parametric production frontier technique.
Keywords: C14; H50; 330; Efficiency; Free Disposable Hull; Government expenditure; Production possibility frontier